Evaluasi Desain Antar Muka Aplikasi Mobile Nusantara Ojek menggunakan Metode Heuristic Evaluation - Dimas Adhitya Rahadiarizki; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Nusantara ojek is application service mobile transportation online developed by Pt Tekno Karya Nusa. Total the downloader already reached 10.000 more with ratings 4.1 from google play . Although the application many been downloaded , but there is still complaint related those service application, which is those application not allow to access. Evaluator that get involved in the process evaluation heuristics in total seven people's. Included nine principles have been used. That is : visibility of system status, offer real world object, user control and freedom, consistency and standarts, error prevention, recognition rather than recall, flexibility and efficiency of use, aesthetic and minimalist design, help user recognize, diagnose and recover from error. Evaluation usability using Method heuristic that can produce in total findings problems that found by seven evaluators. Around about 27 problems that included two catastrophic matters, five big major problems, 14 medium problems, and six minor problems. Needs to be added are chat features with a four severity rating (major). All of those the result of analysis heuristic application mobile nusantara ojek that provide on the average of the severity higher rating using the princip heuristic MA03 (user control and freedom) , with the value 3,69. While the biggest princip found which is MA01 (visibility system status) with percentages 20 percent.